A Total Synthesis of Protoberberine Alkaloids - Fichtner, Harry Robert (My University, 1980)
The synthesis of protoberberines developed in this laboratory by Kiparissides has been studied in greater detail. The key intermediate in this synthesis is formed by the condensation of 3,4-dihydro-6,7-dimethoxy-N-(2,3-dimethoxybenzyl)-isoquinolinium chloride with the anion of methyl methylthiomethylsulfoxide. Careful chromatography of the product has established that it is a complex mixture of diastereomers. The separated fractions were individually cyclized to dihydropalmatine chloride, which was isolated in crystalline form directly from the reaction mixture. This quarternary salt was reduced directly to tetrahydropalmatine, and also used in the synthesis of corydaline.
This work has also shown that isoquinolines may be substituted for 3,4-dihydroisoquinolines as starting materials in the synthetic sequence.
Keywords: Chemistry; Chemistry